2018
DOI: 10.7554/elife.23625
|View full text |Cite
|
Sign up to set email alerts
|

Stromule extension along microtubules coordinated with actin-mediated anchoring guides perinuclear chloroplast movement during innate immunity

Abstract: Dynamic tubular extensions from chloroplasts called stromules have recently been shown to connect with nuclei and function during innate immunity. We demonstrate that stromules extend along microtubules (MTs) and MT organization directly affects stromule dynamics since stabilization of MTs chemically or genetically increases stromule numbers and length. Although actin filaments (AFs) are not required for stromule extension, they provide anchor points for stromules. Interestingly, there is a strong correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
138
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(168 citation statements)
references
References 60 publications
9
138
2
Order By: Relevance
“…Chloroplast clustering around the nucleus has been previously observed during ETI triggered by the p50 protein from TMV (Caplan et al , ; Kumar et al , ). Considering this, we wondered whether expression of Rep could result in the activation of immune responses in N. benthamiana .…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…Chloroplast clustering around the nucleus has been previously observed during ETI triggered by the p50 protein from TMV (Caplan et al , ; Kumar et al , ). Considering this, we wondered whether expression of Rep could result in the activation of immune responses in N. benthamiana .…”
mentioning
confidence: 82%
“…Fondong et al , ; Jelenska et al , , ; Li et al , ; Liu et al , ; Park et al , ; Petre et al , ; Rodriguez‐Herva et al , ; Rosas‐Diaz et al , ; de Torres Zabala et al , ). Intriguingly, chloroplasts can establish contact with the nucleus, through clustering around it and extending tubular stroma‐filled protrusions called stromules (Natesan et al , ), under different circumstances, including the activation of ETI triggered by the p50 protein from Tobacco mosaic virus (TMV) (Caplan et al , , ; Kumar et al , ; Kwok and Hanson, ). Although the exact role of this physical interaction between chloroplasts and nucleus is at present unclear, it has been suggested that this connection could enable the transfer of molecules from the plastids (e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While individual reactions that take place in the plastid or mitochondrion benefit from their compartmentalization, broad metabolic processes are coordinated between them and the rest of the cell (Rolland et al, 2012;Schrader & Yoon, 2007;Sweetlove & Fernie, 2013). Furthermore, plastids and mitochondria physically interact with multiple other cellular compartments, including the nucleus, peroxisomes, and the ER (Barton, Wozny, Mathur, Jaipargas, & Mathur, 2018;Jaipargas, Mathur, Bou Daher, Wasteneys, & Mathur, 2016;Kumar et al, 2018;Kwok & Hanson, 2004;Mueller & Reski, 2015).…”
Section: Introductionmentioning
confidence: 99%